Modelling of intermodal freight transportation network - Vasiliauskas, Aidas V. (Transport, 2002)
It was realized long ago that one of the main factors for steady groowing economic of the country is a properly working transport system in which new enough means of cargo transportation, so called intermodal transportation takes not the last place. First of all it raises problems related with the development and optimization of proper infrastructure – the network of roads and terminals which aim to carry out intermodal transportation. The article deals with one of possible ways of modelling the national intermodal freight transportation network. The basis for such model is the investigation of freight traffic during which we identify the routes for intermodal freight transportation (as well as places where such freight is shifted from one mode of transport to another), extend the existing statistic date base on modal transport carriages and start to develop a new data base on intermodal freight carriages. With the help of the last one we can go further in modelling national intermodal freight transportation network and determine the steps for creating such network. The main steps should include:• the integration of the particular modal networks into a general intermodal network;• the optimization of the network defining optimal routes between possible origin and destination points;• the estimation of terminal operations to get a more detailed and optimal view of the national intermodal cargo transportation network.First Published Online: 19 Dec 2011